2020
DOI: 10.1107/s2052520620007131
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate clusters in minerals: review and complexity analysis

Abstract: Most research on polyoxometalates (POMs) has been devoted to synthetic compounds. However, recent mineralogical discoveries of POMs in mineral structures demonstrate their importance in geochemical systems. In total, 15 different types of POM nanoscale-size clusters in minerals are described herein, which occur in 42 different mineral species. The topological diversity of POM clusters in minerals is rather restricted compared to the multitude of moieties reported for synthetic compounds, but the lists of synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…The filling of the framework cavities by cations and H 2 O molecules more than doubles the complexity tõ 6112 bits per cell. The five most complex mineral structures reflect the basic mechanisms of the generation of crystal-structure complexity of minerals: the formation of nanoscale large polyatomic clusters (usually polyoxometalates (Krivovichev 2020)) and the modular architecture, when the structure is based upon a combination of one or several large modules (Krivovichev 2013a). The high hydration states also favor the high Shannon information content, due to the high number of H atoms.…”
Section: Most Complex Mineral Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The filling of the framework cavities by cations and H 2 O molecules more than doubles the complexity tõ 6112 bits per cell. The five most complex mineral structures reflect the basic mechanisms of the generation of crystal-structure complexity of minerals: the formation of nanoscale large polyatomic clusters (usually polyoxometalates (Krivovichev 2020)) and the modular architecture, when the structure is based upon a combination of one or several large modules (Krivovichev 2013a). The high hydration states also favor the high Shannon information content, due to the high number of H atoms.…”
Section: Most Complex Mineral Structuresmentioning
confidence: 99%
“…is of statistical nature that allows exceptions, but works on a global scale. Recently, it was demonstrated that the Fedorov-Groth law is valid and statistically meaningful, when chemical complexity is expressed according to the equation (5) as the amount of Shannon chemical information per atom and the degree of symmetry as the order of the point group of a mineral (Krivovichev, Krivovichev 2020).…”
Section: Chemical Complexitymentioning
confidence: 99%
“…From the structural point of view, natrophosphate belongs to the family of minerals containing polyoxometalate clusters as recently reviewed in [33]. The presence of the (FNa6) 5+ units at the core of the clusters allows to suggest that the mineral may serve as a precursor for the formation of antiperovskite structure motifs based upon anion-centered octahedra [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is called information density and expressed in bits/Å 3 . Krivovichev with collaborators and followers applied these quantities to study various minerals [91][92][93][94][95][96][97][98][99][100][101] and found the relations between the crystallographic symmetries, size, and information entropy estimates (Table 4) and proposed the classification of the minerals, which is based on their complexity estimated with I values (Table 5). The latter means that the information entropy is associated with the complexity of the minerals (though the authors make a reservation that other approaches to assessing the complexity of the minerals can be used, such as exploiting the approximation of the crystal structures as the nets or invoking algorithmic complexity paradigm [96]).…”
Section: Information Entropy Of Solidsmentioning
confidence: 99%
“…Their original symmetries are reduced upon forming molecular crystals due to the influence of the neighbors of a crystal lattice (Table 6). Note that additional factors in addition to the structural complexity (e.g., layer stacking or complexity of hydrogen network) can be taken into account within the approach described above [97]. Table 6.…”
Section: Information Entropy Of Complex Chemical Objects 41 Information Entropy Of Solidsmentioning
confidence: 99%